Nabel Schau : Im Winter des Jahrtausends. - Altmann, Susanne; Bellut, Clemens; Janecke, Christian; Kunsthalle, Dresden (Dresden : efau Verlag, 1999)
Bachman, Ursula ; Balassanian, Sonia ; Gärtner, Ulrike ; Klekamp, Stefanie ; Kreissl, Alexa ; Kerber, Daniel ; Lutz, Klaus ; Silbermann, Hendrik ; Weible, Eberhard ; Witschi, Hans
19.11.1999 - 10.1.2000 in des Kunsthalle Dresden, art'otel, Dresden
kunstcatalogus